Intervention effect of group counseling on social support and post-stress growth of orphans and vulnerable children in China - Zhang, Lyuci; Wu, Sumei; Roslan, Samsilah; Zaremohzzabieh, Zeinab; Chen, Ye; Jiang, Yuqin (Frontiers in Psychology, 2022)
Orphans and vulnerable children are a vulnerable category of children who are exposed to more stressful circumstances and receive less social assistance than other children. This study aims to investigate the effects of group counseling based on social intervention and psychological therapy (SSGPC) on social support and the perceived stress growth of orphans and vulnerable children. In one special educational needs school in Nanning, China, the SSGPC was developed and implemented. Using the social support scale and the post-stress growth scale, the researchers looked into the effects of the SSGPC on orphans and vulnerable children. Twenty-seven orphans and vulnerable children between the ages of 9 and 12 were assigned to the experimental and control groups at random. A pretest-posttest method of quasi-experimental design was used, with 13 participants in the experimental group and 14 in the control group. The results revealed that the intervention group had significantly higher scores for social support and post-stress growth than the control group. The SSGPC had significantly improved the levels of social support for orphans. The findings indicated that the SSGPC provides an effective way to improve social support and post-stress growth of orphans and vulnerable children.